SEXUAL DIFFERENCES IN PARENTAL FEEDING EFFORT DURING THE NESTLING PERIOD OF THE WHITE-HEADED MARSH-TYRANT (ARUNDINICOLA LEUCOCEPHALA) - Cestari, Cesar [UNESP] (Neotropical Ornithological Soc, Usgs Patuxent Wildlife Research Ctr, 2012)
Parental effort may influence the fitness and survivorship of adult birds and their offspring from one breeding season to the next. Although much is known about parental feeding effort in tyrant flycatchers, many species remain understudied. In this study, I examined parental feeding effort of the White-headed Marsh-Tyrant (Arundinicola leucocephala) at a pond in southeastern Brazil. I conducted 10.3 hrs of observations from two locations: a high place with all view of the whole pond, that allowed me to observe flight distances of parents hunting for prey; and from near the nest to observe frequency of visits to the nest. The female marsh-tyrant flew farther while hunting prey and made more visits to the nest than did the male. The adults (mainly the female) provided a variety of terrestrial and aquatic arthropods to the nestlings. Additionally, parents removed fecal sacs from the nest and nestlings eliminated arthropod remains from the nest, the first records of nest sanitation activities by this species. Nonexclusive hypotheses that may explain the lower level of parental care provided by the male include: higher predation risk due its more conspicuous plumage, commitment of male to territory defense, and its selfish behavior influenced by indirect genotype fitness inherited by the offspring. Accepted 25 June 2012.
Keywords: VVhite-headed Marsh-Tyrant; Arundinicola leucocephala; diet; nesting; offspring; parental care; Tyrannidae